Development of Evaluation Tool Based on Science Literacy on Topics of Water Recycling (Journal of Primary Education, 2019)
The aims of this research were to develop evaluation instrument based on science literacy which was appropriate to be applied, comprehend and easily to be learnt by the students, and functional to identify the capability of scientific literacy among students. The research methods used ADDIE design (Analysis, Design, Develop, Implement and Evaluate). The subjects of the research was the fifth degree students in Gisikdrono 02 Primary School Semarang. Validity test results indicated that the instrument has been valid. The reliability test result gained 0.83 with excelent criteria. The characteristics of evaluation instruments which had developed indicate that the instrument had a proportion of difficulty level in number of 20% easy questions, 55% about moderate, and 25% difficult questions. The results of the differentiation power analysis then combined with the level of difficulty and obtained 30 question items with good quality that can be used. The scientific literacy capability profile tested by the developed instrument showed that the mastery of science literacy in moderate criteria.